Improving Potassium Recommendations for Agricultural Crops 2020
DOI: 10.1007/978-3-030-59197-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Outputs: Potassium Losses from Agricultural Systems

Abstract: Potassium (K) outputs comprise removals in harvested crops and losses via a number of pathways. No specific environmental issues arise from K losses to the wider environment, and so they have received little attention. Nevertheless, K is very soluble and so can be leached to depth or to surface waters. Also, because K is bound to clays and organic materials, and adsorbed K is mostly associated with fine soil particles, it can be eroded with particulate material in runoff water and by strong winds. It can also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
0
13
0
1
Order By: Relevance
“…Nonetheless, N is the most required nutrient by plants and the most mobile nutrient, making it easily lost from the soil through harvested products, leaching, volatilization, erosion, and denitrification if not managed properly (88,139). Potassium, on the other hand, is the third most important nutrient for crops after phosphorus (140). Despite the fact that potassium is abundant in soils, the readily available pool is so small, and the fate of K in soil is almost similar to that of N (141).…”
Section: Status Of Soil Nutrient Balance In Smallholders' Farming Sys...mentioning
confidence: 99%
“…Nonetheless, N is the most required nutrient by plants and the most mobile nutrient, making it easily lost from the soil through harvested products, leaching, volatilization, erosion, and denitrification if not managed properly (88,139). Potassium, on the other hand, is the third most important nutrient for crops after phosphorus (140). Despite the fact that potassium is abundant in soils, the readily available pool is so small, and the fate of K in soil is almost similar to that of N (141).…”
Section: Status Of Soil Nutrient Balance In Smallholders' Farming Sys...mentioning
confidence: 99%
“…It is often bound to clay and other organic substances, and it mostly gets absorbed when attached to fine soil particles. As such, K is prone to erode to rain or wind exposure [88]. Soil typically erodes more in harder rain [89] and harder wind [90].…”
Section: Nutrient Contentmentioning
confidence: 99%
“…It is usually found in natural surface waters under 5 mg/L (Skowron et al, 2018) and between 2 and 3 mg/L in rivers (Lenntech, 2020); the values found in both rivers are higher than that, indicating the use and pollution of freshwater by artificial fertilizers with the Las Palmas river showing higher potassium values than the Colorado river (Table 1). Potassium can be used as an indicator of surface runoff because it is very soluble and can be washed by rainfall into water bodies depending on rainfall intensity and unlike nitrogen, there are no gaseous losses of potassium (Alfaro et al, 2008;Alfaro et al, 2017;Goulding et al, 2020). This potassium runoff is exceptionally high in tropical regions (Acharya et al, 2007).…”
Section: Physical-chemical Parametersmentioning
confidence: 99%